1194 Biomonitoring of health care personnel involved in the preparation and administration of anticancer drugs in three italian hospitals. (24th April 2018) - Ursini, CL; Cavallo, D; Omodeo Salè, E; Fresegna, AM; Ciervo, A; Jemos, C; Maiello, R; Buresti, G; Colosio, C; Rubino, FM; Delrio, P; Maiolino, P; et al.
Abstract : Introduction: Most of anticancer drugs has in common DNA-damaging properties, therefore health care personnel who handle such drugs is at risk for adverse health effects. We aimed to evaluate exposure and its genotoxic and cytotoxic effects in technicians and nurses who prepare and administer anticancer drugs in oncology units of different hospitals. Methods: In the hospitals (A, B, C) we studied 17 pharmacy technicians/nurses who prepare anticancer drugs, 25 nurses who administer them and 53 controls. Workplace monitoring of 5-fluorouracil (5FU) and gemcitabine (GEM) was performed by HPLC-UV on wipes/swabs collected in areas of pharmacy and administering wards. Personal exposure to 5FU and GEM was monitored by pads. We measured urinary metabolite α-fluoro-β-alanine by LC-MS-MS. We calculated total amount of handled drugs. Buccal micronucleus cytome (BMCyt) assay was used to evaluate DNA damage (micronuclei MN and nuclear buds NB), cytokinetic defects (binucleated cells BN) and cell death (as condensed chromatin CC). Results: Drug contamination was found only in the 30% of wipe/swab samples, with GEM more frequently present than 5FU. Contamination didn't show significant difference among the hospitals. Only GEM deposition was found on workers' pads (93% of samples). No α-fluoro-β-alanine was found. Total amount of prepared drugs was similar in A and B and higher than C. B prepared drugs only manually while in A they were prepared automatically/manually. In A and B we found in workers who prepare drugs, higher genotoxicity than respective controls. Total amounts of administrated drugs were in A>B>C. Nurses who administer drugs showed higher genotoxic (%MN) and cytotoxic (%CC) effects than controls in A and C. Conclusion: These findings show that total amount of prepared drugs correlate with higher genotoxicity found in A and B. We also demonstrate the suitability of BMCyt assay as sensitive and no invasive biomarker of early effect for occupational antineoplastic exposure.